2005
DOI: 10.1158/1055-9965.epi-04-0706
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-I, IGF-Binding Protein-3, and Mammographic Breast Density

Abstract: Some studies have suggested that insulin-like growth factor (IGF) pathway is related to premenopausal breast density, one of the strongest known breast cancer risk factors. This study was designed specifically to test the hypothesis that higher levels of IGF-I and lower levels of IGF-binding protein (IGFBP)-3 are associated with high mammographic breast density among premenopausal but not among postmenopausal women. A total of 783 premenopausal and 791 postmenopausal healthy women were recruited during screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
140
4
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(150 citation statements)
references
References 44 publications
5
140
4
1
Order By: Relevance
“…In the present study, we observed a positive association between IGFBP-3 and percent mammographic density, which is in contrast to others [3]. However, the association between IGFBP-3 and breast cancer risk may differ according to whether IGFBP-3 is measured as intact, fragmented or total [52].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, we observed a positive association between IGFBP-3 and percent mammographic density, which is in contrast to others [3]. However, the association between IGFBP-3 and breast cancer risk may differ according to whether IGFBP-3 is measured as intact, fragmented or total [52].…”
Section: Discussioncontrasting
confidence: 99%
“…Ovarian steroid hormones and growth factors, on the other hand, increase cellular proliferation in the breast, which may be reflected through mammographic density. Furthermore, the growth hormone (GH)-insulin-like growth factor-1 (IGF-1) signaling pathway, has been associated with breast cancer [2,3], and IGF-1 is suggested to influence cellular proliferation and inhibit apoptosis through the activation of PI3/Akt pathway, in both normal breast cells and breast cancer cell lines [4,5]. The level of IGF-1 is regulated by GH, and modulated by insulin-like growth factor-binding protein-3 (IGFBP-3).…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, Hartmann et al showed that the success rate of breast augmenting estrogen stimulation was dependent on a subsequent increase of IGF-1 concentrations in the women tested (42). Moreover, high IGF-1 levels have been linked to mammographic density in premenopausal women (43). Mammographic density is significantly associated with breast cancer mortality (44).…”
Section: Discussionmentioning
confidence: 91%
“…It has been suggested that elevated levels of IGF-I may increase breast density and thereby increase the risk of breast cancer. Several studies have shown that elevated circulating levels of IGF-I are directly associated with higher mammographic density in premenopausal women [7][8][9][10], although these findings were not confirmed in all studies [11][12][13]. The association of circulating IGF-I levels with mammographic density was not seen in postmenopausal women [7-9, 11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…IGFBP-3 has also been shown to act independently from IGF-I by inducing apoptosis [16,17]. High circulating levels of IGFBP-3 have been shown to be related to lower mammographic density in premenopausal women [7][8][9], but not all studies confirm this [10,12]. In postmenopausal women no relation was found between IGFBP-3 levels and mammographic density [7][8][9].…”
Section: Introductionmentioning
confidence: 99%